Structural Reform, Stabilization, and Growth in Turkey - Kopits, George (Washington, D.C. : International Monetary Fund, 1987)
Following a severe balance of payments crisis in the late 1970s, in January 1980 Turkey embarked on a far reaching stabilization and structural adjustment program.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet